Nonprimary Cytomegalovirus Fetal Infection - Rodrigues, S. (2016)
Cytomegalovirus (CMV) is the most common congenital viral infection, causing hearing, visual and psychomotor impairment. Preexisting maternal CMV immunity substantially reduces, but not eliminates, the risk of fetal infection and affectation. This article is about a case of nonprimary maternal CMV infection during pregnancy, with vertical transmission, resulting in severe fetal affectation. Preconceptional analysis indicated maternal CMV past infection. Pregnancy progressed uneventfully until the 20th week ultrasound (US), which revealed cerebral abnormalities: thin and hyperechogenic cerebral cortex with prominent lateral ventricles, bilateral periventricular hyperechogenicities, cerebellar vermis hypoplasia and absent corpus callosum. The MRI suggested these findings were compatible with congenital infection rather than primary brain malformation.The fetal karyotype was normal. The title of CMV's IgG antibodies almost tripled. Since the first semester, analysis of the polymerase chain reaction (PCR) for CMV DNA in the amniotic fluid was negative. The pregnancy was terminated at 23 weeks. Neuropathological findings at autopsy showed severe brain lesions associated with CMV infection.